Individual stress reactivity predicts alcohol craving and alcohol consumption in alcohol use disorder in experimental and real-life settings - Zaiser, Judith; Hoffmann, Sabine; Vetter, Sina; Gessner, Tatjana; Deck, Milena; Bekier, Nina Kim; Abel, Martin; Radler, Philipp; Langejürgen, Jens; Lenz, Bernd; Vollstädt-Klein, Sabine; Stallkamp, Jan; et al. (Translational Psychiatry, 2025)
Stress- and alcohol cues trigger alcohol craving and alcohol consumption in alcohol use disorder (AUD). However, their interactions on a physiological and psychological level and their effects on daily alcohol craving and alcohol use in real-life situations are not understood yet. We conducted a randomized-controlled experimental study to compare the effects of psychosocial stress against physical stress and a control intervention, each followed by an alcohol cue-exposure, on alcohol craving, subjective stress and saliva cortisol levels (main outcomes) in N = 121 individuals with AUD and collected data on daily alcohol use and craving during a 1-year ambulatory assessment phase. We applied linear mixed models to compare the effects of experimental interventions on the main outcomes and the relative contributions of the observed changes on the main outcomes to predicting stress and alcohol craving during the experiment and alcohol use and craving during the ambulatory assessment phase. Sequential exposure to psychosocial stress and alcohol cues induced higher cortisol levels (F(10,580) = 10.819, p < 0.001), subjective stress (F(2,117) = 10.520, p < 0.001) and alcohol craving (F(6,348) = 4.313, p < 0.001) compared to the exposure to physical stress and the control condition. Subjective stress reactivity was the most influential predictor of craving during the experiment (F(1,92) = 9.43, p = 0.003) and during the ambulatory phase (β = 0.16, p = 0.039) while cortisol levels predicted alcohol consumption in real-life settings (β = 9.76, p = 0.043). Our results highlight the impact of psychosocial stress on cue-induced craving and subjective and neuroendocrine stress responses and demonstrate links between subjective and neuroendocrine stress-reactivity and alcohol craving and alcohol use in real-life settings.